2013
DOI: 10.1038/sc.2013.140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combined administration of vitamins C and E on the oxidative stress status and programmed cell death pathways after experimental spinal cord injury

Abstract: Study Design: Experimental, controlled, animal study. Objectives: To assess the effects of vitamins C and E (VCE) treatment on oxidative stress and programmed cell deaths after rat spinal cord injury (SCI), as well as functional recovery. Setting: Taiwan. Methods: Fifty-four Sprague-Dawley rats were used for the experimental procedure. In the sham group, laminectomy at T10 was performed, followed by impactor contusion of the spinal cord. In the control group, only a laminectomy was performed without contusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The levels of oxidative stress and apoptosis are believed to be two of the most important factors involved in post-traumatic degeneration due to destruction of the damaged spinal cord. 3 Therefore, decreasing oxidation stress injury and inhibition of apoptosis are key factors in the therapeutic schedule of SCI. Calcitriol, that is 1,25-dihydroxyvitamin D 3 , is the biologically active metabolite of vitamin D and the predominant Ca 2+ -regulatory steroid hormone, 14 which has a major role in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of oxidative stress and apoptosis are believed to be two of the most important factors involved in post-traumatic degeneration due to destruction of the damaged spinal cord. 3 Therefore, decreasing oxidation stress injury and inhibition of apoptosis are key factors in the therapeutic schedule of SCI. Calcitriol, that is 1,25-dihydroxyvitamin D 3 , is the biologically active metabolite of vitamin D and the predominant Ca 2+ -regulatory steroid hormone, 14 which has a major role in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, oxidative stress and apoptosis were shown to be important factors precipitating posttraumatic degeneration due to secondary destruction of the damaged spinal cord. 3 Although the precise molecular pathway of secondary injury is still controversial, therapeutic strategies that inhibit or delay oxidative stress and apoptosis may contribute to SCI recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Therefore, AA has been used for the treatment of many diseases, such as cardiovascular, digestive, respiratory, musclar, immune dysfunction, urogenital and, importantly, neurological diseases. 10,20 In fact, the effect of normaldose AA on SCI was previously investigated, and demonstrated that AA can alleviate the histological features of tissue injury, although it did not show significant effect on the behavioral function of the injured animals. 9 The results suggest that AA has positive effects on SCI; however, its usage at a normal dose has only limited protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,19 One of the vital functions of AA is to clear free radicals, therefore exerting protective effect in various injuries. 12 Therefore, AA has been used for the treatment of many diseases, such as cardiovascular, digestive, respiratory, musclar, immune dysfunction, urogenital and, importantly, neurological diseases.…”
Section: Discussionmentioning
confidence: 99%